Comparison of Intrusive Effects and Amount of Root Resorption in Maxillary Incisors Using Two Conventional Intrusion Arches and Mini-Implants - Shilpa Vinu; Virendra Vadher; Arvind Nair; Shalabh Baxi; Shweta Singh; Chhaya Barapatre (Journal of Pharmacy and Bioallied Sciences)
Aim and Objective: This study aimed to compare the amount of maxillary incisor intrusion and root resorption using three methods: mini-implants, utility arches, and Connecticut intrusion arches. Materials and Methods: Eighteen patients aged 15 to 25 years with deep bite were divided into three groups: 10 patients each for mini-implant, utility arch, and Connecticut intrusion arch groups. Bilateral mini-implants were used in Group 1, while utility and Connecticut arches were used in Groups 2 and 3, respectively. Intrusion was performed over four months. Lateral cephalograms and orthopantomograms were taken at the start (T1) and after four months (T2). Results: The mean incisor intrusion measured by U1-PP was 2.08 mm in Group 1, 1.55 mm in Group 2, and 1.75 mm in Group 3 (P < 0.05). CR-PP measurements showed 1.91 mm in Group 1, 1.56 mm in Group 2, and 1.66 mm in Group 3 (P < 0.05). Incisors in Group 1 showed minimal protrusion compared to significant protrusion in Groups 2 and 3 (P < 0.05). Maxillary molars showed no significant changes in Group 1 but distal tipping in Groups 2 and 3 (P < 0.05). No root resorption was observed in any group. Conclusion: Mini-screws demonstrated the most effective maxillary incisor intrusion with minimal side effects compared to utility and Connecticut intrusion arches.